Pelatihan Pemasaran Digital pada Usaha Rumah Tangga di Desa Bukit Peninjauan I Kabupaten Seluma - Rita Feni; Maheran Mulyadi; Edy Marwan; Jon Yawahar; Anton Feriady; Neti Kesumawati; Surya Ade Saputra (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aims to provide counseling and training for housewives and home-based business actors in Bukit Peninjauan I Village, Seluma District, on the utilization of digital marketing for home-based enterprises. The main issue faced by the partners is the limited knowledge and skills in applying digital marketing technologies, particularly social media, to promote their products. The program was implemented through counseling sessions on the benefits of digital marketing and hands-on training on creating digital marketing content for product promotion. The participants consisted of housewives and owners of home-based businesses. The results indicate a high level of partner satisfaction, ranging from 90% to 100%. Specifically, 90% of participants stated that the program met their needs and enhanced their knowledge, 95% expressed satisfaction with the responsiveness of the presenters and the supporting facilities, and 100% showed interest in marketing their products through social media.